2012
DOI: 10.1089/hyb.2011.0100
|View full text |Cite
|
Sign up to set email alerts
|

Anti-caveolin-1 Antibodies As Anti-Prostate Cancer Therapeutics

Abstract: Caveolae are critical cell surface structures important in coordinated cell signaling and endocytosis. One of the major proteins of caveolae is caveolin 1 (Cav-1). Cellular levels of Cav-1 are associated with cancer progression. In prostate cancer cells, levels of Cav-1 are positively correlated with tumor progression and metastasis. Cav-1 can be secreted by prostate cancer cells into the microenvironment and triggers proliferation and anti-apoptosis of the tumor and tumor endothelial cells. Clinical studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Of note, recent investigations revealed that blocking the secreted Cav1 by polyclonal antibodies inhibited the growth of experimental prostate tumors in mice. 70 Nevertheless, the accelerated growth of the untreated prostate tumors in the Cav1-deficient background hints to a potential risk of treatment strategies targeting endothelial Cav1 for improving the radiation response in these tumors. Though increased tumor growth in Cav1 knockout mice is expected be rather a long-term effect of Cav1-deficiency, these observations make a careful validation of such treatment strategies with respect to adverse growth promoting effects absolutely necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent investigations revealed that blocking the secreted Cav1 by polyclonal antibodies inhibited the growth of experimental prostate tumors in mice. 70 Nevertheless, the accelerated growth of the untreated prostate tumors in the Cav1-deficient background hints to a potential risk of treatment strategies targeting endothelial Cav1 for improving the radiation response in these tumors. Though increased tumor growth in Cav1 knockout mice is expected be rather a long-term effect of Cav1-deficiency, these observations make a careful validation of such treatment strategies with respect to adverse growth promoting effects absolutely necessary.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Furthermore, anticaveolin-1 antibodies to neutralize circulating caveolin-1 have been suggested as potential therapy in prostate cancer. 7 As caveolin-1 is an essential structural component of plasma membrane caveolae, cholesterol-rich-invaginated pits at the plasma membrane, 8 it has been assumed that caveolin-1 in prostate cancer cells forms caveolae. However, we recently demonstrated that the caveolin-1-positive prostate cancer cell line PC-3 lacks caveolae because of the absence of an essential co-factor cavin-1 (also known as PTRF; polymerase I and transcript release factor).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry revealed granular CAV-1 and PC cytoplasmic staining with lower Gleason scores (grade 6) and showed lower protein expression than in higher Gleason score PC. In humans, CAV-1 expression is positively correlated with high-grade Gleason scores, early recurrence time and therapeutic resistance (Karam et al, 2007;Kuo et al, 2012;Quest et al, 2013).…”
Section: Discussionmentioning
confidence: 99%